Building a Ukrainian Identity in Odessa: Negotiation of Markers and Informal Nationalism - Abel Polese (Department of Government Studies Universitas Muhammadiyah Makassar, 2018)
A large and established body of literature on nation building in post-socialist spaces has initially put emphasis on state-centred construction of identity references and markers such as language, education or institutions and governance. In contrast, a recent stream of scholarship has attempted to bring agency into identity debates to propose new tools and approaches that can be used in the study of identity construction. This article is a further exploration of the latter position. It looks at the way identities are constructed, and renegotiated, at the everyday level, by ordinary people, by illustrating the competition between Russian and Ukrainian languages in Odessa, a Ukrainian city on the Black sea, to look at the synergy generated by the competition between local and national narratives.